Sistem Pengunci Pintu Berbasis Website - Gustama, Rifky Wanda; , Dr. Heru Supriyono,M.Sc (2017)
The most widely used key majority communities is the key to a mechanical slot. Locks of this type has its drawbacks, one of which is the absence of a history list of key usage. Based on this, the authors innovate to create technology design model locking system which is connected with the website as a WiFi interface. The purpose of this study is to provide facilities in the room door lock automatically with only internet access without having to do it manually. It also can display the data history of each operation of the locking system that can be printed in the form of a document with a file format. Its main components are the Arduino UNO as a controller system that controls the servo motors are simulated with Light-Emitting-Diode (LED). From the test results, serial COM as an intermediary server and can run optimally arduino to run the system. The maximum range of the WiFi signal from the server to the user after using the virtual application hotspot extend repeater is 30 meters on the cubicle wall with a thickness of 15 centimeters. All activity logs any system capable of accurately displayed by the website. Keywords: Arduino UNO, Website, WiFi, LED, Security